Biliary tract abnormalities in patients with autosomal dominant polycystic kidney disease: Incidence and magnetic resonance cholangiopancreatography findings - Murat GÜRSOY; Beril AKMAN; Muhteşem AĞILDERE; Aslı DOĞRUK; Cüneyt AYTEKİN and Nurhan ÖZDEMİR and Sedat BOYACIOĞLU (Turkish Journal of Gastroenterology, 2019)
-